An inquiry into the effect of voluntary counseling and testing on mitigating the spread of HIV and AIDS among high school teachers teaching in Mdantsane - Nkwateni, Luleka Letticia (Stellenbosch : University of Stellenbosch, 2010)
Thesis (MPhil (Industrial Psychology. Africa Centre for HIV/AIDS Management))--University of Stellenbosch, 2010.